Marketing Strategy at Sukmojati Coffee using Blue Ocean Strategy - Rifana Rizki Maulida; Mubarokah Mubarokah; Ika Sari Tondang (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Agroindustry plays a role in supporting local economic growth and job availability. Sukmojati Coffee is a local coffee agroindustry in Prigen District, Pasuruan, that processes local coffee beans typical of Mount Arjuna into ground coffee. In its development, Sukmojati Coffee faces increasingly tight competition in the coffee industry, with many competitors that cannot be avoided. To maintain a business amid competition, a marketing strategy is essential. This study aims to analyze Sukmojati Coffee's marketing strategy. This study was conducted from March to May 2025. Data collection was carried out through questionnaires completed by 100 respondents and in-depth interviews with a purposively selected informant. The collected data were analyzed using the Blue Ocean Strategy framework. The results of the study showed that Sukmojati Coffee obtained the highest scores on four factors, namely price (3.40), promotion (3.69), service (3.85), and ordering (3.71), and obtained the lowest scores on three factors, namely product (3.37), place (3.09), and store (2.82). Based on the strategy canvas and four-action framework, the marketing strategies that can be implemented are improving packaging performance, improving sales through marketplaces, improving store performance, and creating experiential marketing-based services. Three tiers of non-customers can be turned into customers through 3 marketing strategies: increasing product variety, creating 3-in-1 coffee products, and marketing Sukmojati Coffee as souvenir items. Based on the buyer utility map, Sukmojati Coffee created five new utilities and eliminated the pain points consumers had been facing. These results emphasize the importance of value innovation for Sukmojati Coffee consumers, both functionally and emotionally, to attract consumer attention and increase sales volume.